DEVELOPING WEB-BASED LEARNING MEDIA TO FOSTER LITERACY IN HIGHER EDUCATION - Inharjanto, Anselmus; Lisnani, Lisnani (Universitas Muhammadiyah Metro, 2024)
The research aims to develop web-based learning media to foster literacy in higher education that is valid, practical, and potentially effective. Besides, this study attempts to obtain the average literacy score using the developed web-based learning media. The researchers employed the ADDIE model of instructional design comprising five phases: analysis, design, development, implementation, and evaluation. The research subjects were university students of Musi Charitas Catholic University, particularly the English Language Education Study Program students. The data collecting technique employed tests, questionnaires, and documentation. The collected data was analyzed by using qualitative descriptive analysis and thematic analysis. The research results show that web-based learning media on literacy using Google Sites is categorized as valid and practical and has potential effects. The result shows that the average literacy score is 84.8. Thus, web-based learning is likely to foster literacy in the context of higher education.